Effectiveness of Dapagliflozin in Treating Type 2 Diabetes Mellitus in a Real-World Indian Setting - Uday M. Jadhav; Manoj Chawla; Sandeep Rai; S. Manjula; M. Krishna Kumar (Journal of Diabetology)
Aims and Objectives: Dapagliflozin has an abundance of real-world evidence from North America and Europe, however, there is still a dearth of data specifically on the Asian population. This study was conducted to assess the effectiveness of dapagliflozin among Indian patients with type 2 diabetes mellitus (T2DM) and to examine its practical application in a real-world Indian clinical setting. Materials and Methods: This single-arm, open-labeled, multi-centric observational study included patients with T2DM from various clinical settings across India. The primary endpoint was the changes in glycated or glycosylated hemoglobin A1C (HbA1c; %) and body weight from the baseline to week 12 where the secondary endpoints were changes in fasting blood sugar (FBS) and post-prandial blood sugar (PPBS) at baseline, week 4, and week 12. Results: The study included 1549 diabetic patients from different regions of India, with an average age of 53 years. Dapagliflozin treatment resulted in a substantial reduction in HbA1c and weight from baseline to week 12 (P < 0.0001). Furthermore, a substantial decrease in FBS and PPBS from baseline to week 12 was noted following dapagliflozin administration (P < 0.0001). In addition, a significant mean reduction in body weight was observed in patients from baseline (69.32 kg) to week 12 (67.39 kg, P < 0.0001). Conclusion: Dapagliflozin treatment resulted in a significant reduction in HbA1c, body weight, FBS, and PPBS over 12 weeks in patients with T2DM, thereby corroborating the potential usefulness of dapagliflozin as a therapeutic option for managing diabetes.